How Intellectual Capital Can Develop Innovation And Performance Of Accounting Study Program? - Sigit Hermawan; Niko Fediyanto; Wiwit Hariyanto; Prasetyo Utomo; Amelia Nugraha Dini (Universitas Muhammadiyah Malang, 2023)
Purpose: The purpose of this study is to explore the role of intellectual capital in developing innovation and performance of accounting study programs in Indonesia Methodology/approach: This type of research is qualitatively interpretive. Because the researcher understands the meaning contained in the interpretation of key informants. Findings: Human Capital is a key factor for intellectual capital to develop innovation and performance of accounting study programs. IC, both integrated and individually, plays a role in improving the performance of IAPS 4.0-based study programs Practical implications: The results of this research can be used by the head of the accounting study program in achieving superior accreditation based on IAPS 4.0, namely by utilizing the role of intellectual capital in developing innovation and performance. Originality/value: The originality of this research is to explore the intellectual capital component associated with the innovation component and the performance component of the IAPS 4.0-based accounting study program. This research also explores basic theories such as role theory, human capital theory, and the resources-based theory.